Addisonian-like crisis in congenital hypopituitarism and cholestatic jaundice - Lee, Way Seah; Lum, L.C.; Harun, F. (Malaysian Medical Association, 2003)
A six-week-old male infant was admitted for investigation of cholestasis and pale stools. He became lethargic and apnoeic with prolonged seizures after a percutaneous liver biopsy. Subsequent investigations showed conjugated hyperbilirubinaemia, elevated liver enzymes, and hypoglycaemia. The radinuclide hepatobiliary scintigraphy was non-excretory. After an operative cholangiogram, the infant developed Addisonian-like crisis with bradycardia, hypotension, respiratory distress, metabolic acidosis, hypoglycaemia, hyponatraemia, and hyperkalaemia. Blood investigations confirmed congenital hypopituitarism. Hormone replacement therapy with L-thyroxine and cortisone acetate resulted in dissolution of jaundice and the reduction of the liver size.